Design of a Strategy for the Sustainable Development of the Bakery Industry in Medan City - Tania Alda; Ahmad Shalihin; Chindy Elsanna Revadi; Fadylla Ramadhani Putri Nasution; Raja Ahsan Andifa; Natalia Sri Fifani Br Tarigan; Mhd Irsan; Andreas Pandapotan; Jasmine Meilani Halim; Ranti Widya Ningsih (Engineering Proceedings, 2025)
Medan City has excellent potential to develop small and medium industries. One of the industries that has potential is the bakery industry. Based on the data obtained, it is known that the small-scale bakery industry dominates by 86%. To create a competitive bakery industry, the products must be varied, innovative, good quality, follow market needs, and follow the eco-friendly production process. Based on this, the right strategy is needed so that the bakery industry can develop and increase its competitiveness towards sustainability. This research aims to create a strategy design that the bakery industry can implement to improve competitiveness and productivity toward sustainability. Based on the IFE and EFE matrix results, the bakery industry in Medan City is in quadrant IV, namely in the growth and built position. The right strategy, namely a market penetration strategy, and also a strategy for product development, is required. Based on the results of the QSPM matrix, the strategy with the highest score was obtained, namely, improvement in production processes in the bakery industry through the efficient and eco-friendly production process.